EVALUASI EFEKTIVITAS PROGRAM WORKSHOP PENGEMBANGAN PROFESIONAL GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA MENGGUNAKAN MODEL CIPP - Elok Maziyyah Zulaicho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of the Merdeka Curriculum requires teachers to possess strong professional competencies to design and implement student-centered learning effectively. One strategy employed to enhance these competencies is professional development workshops. However, the effectiveness of such programs needs to be comprehensively evaluated to determine their success and provide recommendations for future improvement. This study aimed to evaluate the effectiveness of a Teacher Professional Development Workshop in Supporting the Implementation of the Merdeka Curriculum at MTsN 6 Nganjuk using the Context, Input, Process, Product (CIPP) evaluation model. The study employed a qualitative approach with an evaluative research design. Data were collected through interviews, observations, and documentation involving the principal, workshop organizers, facilitators, and participating teachers. Data analysis consisted of data reduction, data display, conclusion drawing, and source and technique triangulation to ensure data credibility. The findings indicate that the context component was categorized as good because the program was designed based on teachers' actual needs and aligned with the implementation of the Merdeka Curriculum. The input component was also categorized as good, supported by competent facilitators, appropriate learning materials, participant readiness, and adequate facilities, although limitations in budget allocation and training duration remained. The process component demonstrated that the workshop was implemented according to plan, supported by interactive learning methods and active participant engagement, despite requiring improvements in time management and post-workshop mentoring. Furthermore, the product component revealed improvements in teachers' competencies in developing teaching modules, authentic assessments, differentiated instruction, and Higher Order Thinking Skills (HOTS)-based assessment instruments, as well as strengthening collaborative professional learning among teachers.